2007
DOI: 10.1213/01.ane.0000270215.86253.30
|View full text |Cite
|
Sign up to set email alerts
|

A Survey of Propofol Abuse in Academic Anesthesia Programs

Abstract: Propofol abuse in academic anesthesiology likely has increased over the last 10 yr. Much of the mortality is in residents. Most programs have no pharmacy accounting or control of propofol stocks. This may be of concern, given that all programs reporting deaths from propofol abuse were centers in which there was no pharmacy accounting for the drug.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
88
0
15

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 119 publications
(107 citation statements)
references
References 22 publications
4
88
0
15
Order By: Relevance
“…Although propofol may not appear as a traditional drug of abuse, a survey conducted amongst academic anesthesiology programs in the United States showed a fivefold rise in the rate of its abuse from 1995-2005; furthermore, 28% of these cases were detected only following death due to overdose, indicating a largely unrecognized problem. 21 We also found an alarming percentage of cases of substance abuse (12.5%) that were unrecognized until a fatality occurred. Data is presented as count (%) of 24 cases reported Table 3 Practices Our figures highlight the ongoing challenge of rehabilitating physicians with known previous substance abuse.…”
Section: Discussionmentioning
confidence: 78%
“…Although propofol may not appear as a traditional drug of abuse, a survey conducted amongst academic anesthesiology programs in the United States showed a fivefold rise in the rate of its abuse from 1995-2005; furthermore, 28% of these cases were detected only following death due to overdose, indicating a largely unrecognized problem. 21 We also found an alarming percentage of cases of substance abuse (12.5%) that were unrecognized until a fatality occurred. Data is presented as count (%) of 24 cases reported Table 3 Practices Our figures highlight the ongoing challenge of rehabilitating physicians with known previous substance abuse.…”
Section: Discussionmentioning
confidence: 78%
“…An American survey conducted via email and telephone calls to the chairs of the Anesthesia Departments to detect the prevalence of propofol abuse in 126 Anesthesiology residency programs revealed that 18% of the programs reported one or more cases of propofol abuse over the last decade 27 . This figure represents a fivefold increase if compared to the previous survey.…”
Section: Propofolmentioning
confidence: 99%
“…According to the survey conducted by Wischmeyer et al 27 , among the 16 residents dependent on propofol, six died, three abandoned Medicine and five entered other specialties. Only two residents remained in the field of Anesthesiology.…”
Section: Consequences Of Controlled Substance Abuse By Anesthesiologistsmentioning
confidence: 99%
“…The commonly abused drugs include opioids (morphine, fentanyl and sufentanil), propofol, ketamine, sodium thiopental, lidocaine, nitrous oxide, and the potent volatile anaesthetics [9].…”
mentioning
confidence: 99%
“…There is a higher incidence of death among substance-abusing anaesthesiologists due to the high potency and low therapeutic windows of drugs available for abuse to them like opioids, propofol, and volatile anesthetics [15,16].…”
mentioning
confidence: 99%